Analisis Kemampuan Komunikasi Matematis Secara Tertulis dalam Pembelajaran Saintifik - Akbar, Lalu Ajimuliardi; Ramdaniati, Baiq Kamelia (MAN 4 Kota Pekanbaru, 2024)
Mathematics communication skills are an essential aspect of math pedagogy, notably in the context of scientific learning. This study aims to describe students' performance in conveying math concepts in writing within the scientific learning context by focusing on three groups of students according to their level of mathematical communication skills: high, medium, and low. Based on the results, it is suggested to conduct further in-depth studies, including a more detailed analysis of the factors that influence students' mathematical communication skills in scientific learning. Furthermore, more effective learning strategies should also be developed to improve the students' mathematics communication skills, both oral and written. This further study could provide a deeper insight and be valuable for curriculum development and mathematics learning activities.